Pengaruh Indeks Pembangunan Manusia (Ipm), Upah Minimum Regional (UMR), Dan Tingkat Pengangguran Terbuka Terhadap Jumlah Penduduk Miskin Di Indonesia Tahun 2017-2021 (Studi Kasus 34 Provinsi Di Indonesia) - Novia Rahmawati; Panji Kusuma Prasetyanto; Fitrah Sari Islami (Convergence: The Journal of Economic Development, 2022)
TThis study aims to analyze the effect of the Human Development Index (HDI), Regional Minimum Wage, and Open Unemployment Rate on the Number of Poor Populations in 34 Provinces in Indonesia in 2017-2021. The data used in this study are secondary data obtained from Central Bureau of Statistics (BPS). The technique used in this research is panel data regression analysis through the E-views 10 program. The results show that the Fixed Effect Model (FEM) is the most appropriate panel data regression model. Based on the simultaneous test, the Human Development Index (IPM), Regional Minimum Wage, and the Open Unemployment Rate affect the Number of Poor Populations. Based on the partial test, the Human Development Index (HDI) has a negatif and significant effect on the Number of Poor Populations, while the Regional Minimum Wage (UMR), and the Open Unemployment Rate have a positif and significant impact on the Number of Poor People in 34 Provinces in Indonesia in 2017-2021.   Keywords: HDI 1, Minimum Wage2, Unemployment3, Number Of Poor People 4